Unstable Oxygen Supply and Glaucoma - Konieczka, K.; Fränkl, S.; Todorova, M. G.; Henrich, P. B. (Klinische Monatsblätter für Augenheilkunde, 2014)
The pathogenesis of the glaucomatous optic neuropathy (GON) is an ongoing bone of contention. While the role of intraocular pressure (IOP) is well known, it is also clear that a variety of other factors, particularly those of a vascular nature, are involved as well. In contrast to other eye diseases, it is an unstable oxygen supply, as opposed to chronic hypoxia, that contributes to GON. The major cause of fluctuations in the local oxygen tension is an unstable ocular blood flow (OBF). OBF, in turn, fluctuates if the IOP spikes, blood pressure drops, or OBF autoregulation is defective. The main reason for disturbed autoregulation is a primary vascular dysregulation (PVD), particularly in the context of the so-called Flammer syndrome. Unstable oxygen tension leads to local oxidative stress with many detrimental effects, such as the activation of glial cells, which alters their morphology and gene expression. As a consequence, the local concentrations of nitric oxide and the metalloproteinases increase. The metalloproteinases digest extracellular matrix and thereby contribute to tissue remodelling. The short-lived nitric oxide easily diffuses into the neighbouring neuronal axons, allowing a fusion with the superoxide anion and thereby generating the cell-damaging peroxynitrite. Both this tissue remodelling and damage of the axons contribute to the development and progression of GON.
Keywords: glaucoma; unstable oxygen supply; primary vascular dysregulation; Flammer syndrome